Registros das posturas e movimentos da cabeça, tronco superior e braços na execução das atividades de vida diária em indivíduos com DPOC - Paez, Aline Neves (2017)
Introduction: As static postural alterations in individuals with COPD stand out: cervical kyphosis, abducted and rotated shoulder blades and protruded shoulders, due to the use of accessory breathing muscles, a significant increase in anterior pelvic scale angulation, posterior pelvic deflection and thoracic kyphosis compared to healthy individuals. Objectives: To evaluate and compare the postures and movements of the head, upper body and arms, as well as the angular velocity and the actual performance adopted during activities of daily living (ADL) in healthy and COPD individuals. In addition to evaluating and comparing these postures and movements in ADL performed without and with the use of energy conservation techniques (ECT) in COPD. Methods: Twenty subjects with moderate to very severe obstructive pulmonary disease (COPDG) and 20 healthy subjects (CG) were evaluated through spirometry and two ADL tests, which included: bathing (ADL-BW), putting groceries above the shoulder girdle and below the pelvic girdle, sweeping, stretching, picking up from the clothesline and folding clothes (ADL-CC) performed with record of postures and/or movements of the head, upper body and arms by means of inclinometry. Only the COPDG performed the ADL without and with the use of ECT. Results: The severe COPDG presented lower upper body flexion considered statistically and clinically relevant, as well as lower angular velocity of upper body and arms in the ADL-BW and ADL-CC than the CG. The use of ECT provided lower flexion-extension of the head, upper body and lower arm elevations in all ADL. Also, the ADL performed using the ECT were less dynamic for the upper body and right arm. Conclusion: The severe COPDG presented lower upper body flexion and less dynamic posture in attempt to minimize the dyspnea's sensation, muscular fatigue and hypoxemia. The less dynamic postures adopted in ADL with the use of ECT in individuals with COPD help to minimize the present ventilatory limitation, with consequent lower energy expenditure